Karakterisasi Koleksi Plasma Nutfah Tomat Lokal dan Introduksi - Nazirwan Nazirwan; Anung Wahyudi; Dulbar Dulbar (Politeknik Negeri Lampung., 2014)
The function of plant introductions among others is to obtain new cultivars. After the introduction of plants through the process of adaptation and selection can be used as material crosses with cultivars that have adapted well. A cultivar is said superior when it has a high yield, good fruit quality, resistance to pest attack (plant pests), and able to adapt to various environments grow. The aim of this study was obtain a description, test and compare the yield and quality potential of eight varieties of tomatoes grown in the lowland which are expected to serve as a cross parent material in breeding programs. The experiment was arrange by randomized block design with three replications. The data were analyzed using F-test and the results were significantly midpoint test using LSD test at 5% level. Based on observations on eight strains of local tomatoes and introductions have descripted then selected three strains of tomato introductions which has the form of a round (TM 130804, TM 130805, TM 130806) as well as the introduction of two strains of tomato fruit has an oval shape (TM 130801 and TM 130803 ) that can be used as breeding material further. Keywords : collection, germplasm, tomato.